Performative revolution in Egypt an essay in cultural power - Alexander, Jeffrey C. 1947-4eauthor. (London Bloomsbury Academic, 2011)
The author examines what was new about Egypt's revolution in spring 2011 - why it was so compelling to watch, what made it so effective and does it have implications for democratic movements internationally?
Includes bibliographic references (p. 119-134) and index.
Keywords: Social media -- Political aspects -- Egypt; Power (Social sciences) -- Egypt; Egypt -- History -- Protests, 2011-.; Egypt -- Politics and government -- 1981-.; Egypt -- Social conditions -- 1981-.